Multiscale simulation of history-dependent flow in entangled polymer melts - Murashima, T; Taniguchi, T (Europhysics letters, 2011)
Predicting the flow of an entangled polymer melt is still difficult because of its multiscale characteristics. We have developed a novel multiscale simulation technique to investigate the history-dependent flow behavior of entangled polymer melts. The technique involves using a smoothed particle hydrodynamics simulation that is coupled at each fluid element to microscopic simulators that can accurately account for the dynamics of entangled polymers. The multiscale simulation is used to investigate the flow of an entangled polymer melt around a cylindrical obstacle subject to periodic boundary conditions. It is found that the macroscopic flow behavior is dependent on the history of the microscopic states of the polymers and that this memory causes nonlinear behavior even in the regions where the local Weissenberg number defined using the local strain-rate is less than unity. The spatial distribution of the entanglements ⟨Z⟩ suggests that, in a region around the obstacle, a slight depletion of the entanglements is observed and that this region broadens along the downstream direction. The totality of the presented results suggests that we have succeeded in describing the entangled polymer melt flow without using any constitutive equation.